PENINGKATAN PRODUKTIVITAS DAN PENDAPATAN PETANI CABE MERAH MELALUI PENERAPAN TEKNOLOGI PEMUPUKAN ORGANIK DI KABUPATEN LAMPUNG SELATAN - Asnawi, Robet; Mulyanti, Nina (Publikasi Penelitian Terapan dan Kebijakan, 2012)
Red chilli is one of the many types of vegetables consumed by most people of Indonesia. Problems red chilli farm productivity and incomes are low, it caused by has not been applied correctly technology package, pests and diseases. The objective was to analyzed of increasing productivity and red chilli farming income through application of organic fertilizer package at SouthLampung. This research was conducted in the Sidoreno village, Way Panji sub district, South Lampung regency from July 2010 until December 2010. The treatments were applied organic fertilizer technology package, semi-organic, and farmers technology. The result shows that application of organic fertilizer technology produces the highest production of red chilli (6988,8 kg/ha) compared with semi-organic technology package (6688,8 kg/ha) and farmers' technology package (3460,8 kg/ha). Application of organic fertilizer technology packages increased production by 101,94% and semi-organic fertilizer 93,27% compared with farmers' technology packages. Red chilli farm income through the application of organic fertilizer technology packages producerevenue Rp.71.710.963,- with R/C ratio of 3,12 or increasing of 222,54% compared with farmers' technology package, while semi-organic technology package produce Rp.68.008.369,- with R/C ratio of 3,09 or increasing of 205,89% compared with farmers' technology packages. Breakeven price and breakeven production of farmers’ technology package with a red chili organic fertilizer is 2.375 kg/ha and Rp.3.133,-/kg, semi-organic technology package 2.302 kg/ha and Rp.5.176,-/kg, and farmers’ technology package 2.096 kg/ha and Rp.8.970,-/kg.